(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we establish the global regularity of 2D leray-alpha regularized tropical climate models. The global strong solution to the system with a half Laplacian of the first baroclinic model of velocity (Λ v) and thermal diffusion (-Δθ) or with only the dissipation of the barotropic mode (-Δ u) are obtained.